Behaviour of steel–concrete composite girders under combined negative moment and shear. (April 2021) - Men, Pengfei; Zhou, Xuhong; Zhang, Zhengxu; Di, Jin; Qin, Fengjiang
Abstract: Existing studies on the behaviour of steel–concrete composite girders under combined bending and shear are mainly focused only on composite beams with compact sections; very few studies have investigated slender composite girders, which are commonly used in bridge engineering. Therefore, the behaviour of slender steel–concrete composite girders under combined negative moment and shear were investigated experimentally and numerically in this paper. With the moment/shear ratio, reinforcement ratio, connection type, and web thickness as the experimental parameters, experiments were conducted on seven simply supported composite girders subjected to negative moment and shear. The test results showed that reinforcement ratio, concrete slab thickness, and web thickness significantly influence the ultimate load and failure modes of composite girders; the connection type only slightly influences the behaviour of full-shear-connection composite girders under combined negative moment–shear interaction. All the test data were outside the moment–shear interaction curve of Eurocode 4, i.e. Eurocode 4 tended to produce safer results. Then, a nonlinear finite element model was developed and validated using the experimental results. The factors affecting the moment–shear interaction of composite girders in negative-moment zones were studied through numerical simulation. The numerical results showed that the negative moment–shear interaction law changes little with the change of reinforcement ratio or slab thickness. The web depth-to-thickness ratio significantly influences the negative moment–shear interaction law, and the higher the web depth-to-thickness ratio, the earlier the composite girder begin experiencing moment–shear interaction. Graphical abstract: Unlabelled Image Highlights: Behaviour of slender steel-concrete composite girders under moment–shear is studied. Composite girders with different experimental parameters were tested A finite element (FE) prediction model is developed and validated. Slab & web thicknesses greatly affect composite girder capacity and failure mode. Web depth–thickness ratio greatly affects composite girder moment–shear interaction.